Demonstration of Improved Effectiveness Factor of Catalysts Based on Hollow Single Crystal Zeolites. Issue 20 (28th August 2018) - Pagis, Céline; Meunier, Frédéric; Schuurman, Yves; Tuel, Alain; Dodin, Mathias; Martinez‐Franco, Raquel; Farrusseng, David
Abstract: Pt/NaY zeolites with bulk and hollow morphologies have been used as model catalysts in the hydrogenation of cyclohexene as model reaction. In contrast to most hierarchical zeolites, the presence of a single internal cavity modifies only the mean diffusion length, without changing the external surface area and the crystal size. Differences in catalytic activities have been attributed to a shorter diffusion length in hollow crystals. The volume fraction of zeolite used in bulk crystals (ca. 0.63–0.70) matches well with the shell thickness in hollow crystals, leading to an efficiency factor value for the latter close to 1. Abstract : No core needed ! Why keep unused parts of catalysts? Removing the poorly accessible core of NaY crystals supporting Pt enabled the increase in the effectiveness factor of cyclohexene hydrogenation from 0.63 to 0.97, thus limiting the need of rare and expensive noble metals.